واقع زراعة الأشجار المثمرة المهملة في سورية عموماً والساحل السوري خصوصاً (Latakia University Journal -Biological Sciences Series, 2013)
ازداد الاهتمام على نحوٍ كبيرٍ في زراعة الأشجار المثمرة في جميع أنحاء العالم في السنوات العشرين الأخيرة ، وذلك كنتيجة طبيعية لاتضاح قيمتها الغذائية الكبيرة، إضافة إلى كونها مصدراً جيداً للدخل. ونظراً لأهميتها الاقتصادية فقد تعددت  الدراسات والبحوث التي تناولت زراعتها وتنوعت. وتشغل الأشجار المثمرة بأنواعها المختلفة موقعا هاما في سورية.  فهي تنتشر في جميع محافظات سورية، ولكن بنسبٍ متفاوتة، وازدادت مساحتها من نحو 798 ألف هكتار في عام 2000 لتصل إلى 990ألف هكتار في عام  2010  . [7] وتتميّز سورية بتنوع أنظمته البيئية مما يتيح توفر إمكانيات بيو مناخية متعددة لزراعة أنواع وأصناف متعددة من الأشجار المثمرة ، إضافة لما هو منتشر حالياً، والتي يمكن تطويرها من خلال توصيف الأصناف والطرز الموجودة، ثم تحسينها وراثياً، وتحقيق الاستفادة المثلى من كامل تلك الإمكانيات للوصول إلى معدلات إنتاج مرتفعة .[5] ففي مجال الأشجار الحراجية مثلاً يمكن التوسع كثيراً في زراعة الغار والصنوبر الثمري والكستناء والخرنوب, والسماق وغيرها. وفي مجال الفاكهة فإن إمكانيات التوسع أكبر بكثير؛ إذ تتوفر الظروف المناسبة لزيادة مساحة العديد منها وفي مقدّمتها التوت والبلح والزعرور والعناب والأكي دنيا وحب الأس والأجاص البري والكاكي وغيرها...[6] و[10] During the last twenty years there was an increased  interest to large extent in crowing up the fruitful trees all over the world. That is a natural result of knowing its high feeding value beside its being good source for income. Due to its economical importance, there was variety of searches and studies which approached its farming. The fruitful trees in their different types occupy an important position in the Syrian Agriculture. It spreads at all the provinces  in Syria but in disparate degrees . its square has increased from about 798 000  in year 2000  to become 990 000 hectare  in year 2010 . Our country is distinguished for the variety of  its environmental systems which provides various bioclimatic possibility to grow several types of the fruitful trees in addition to what is available presently , which may be developed by describing and classifying the available  types and  kinds , then to be improved hereditarily and fulfilling the ideal benefit from all these possibilities to perform  high production  rates. In the field of forester trees for example we can go widely in growing laurel, fruitful pine, chestnut, carob , sumac and other kinds . in the field of fruits , the possibility of expanding is more wide where there are suitable conditions to increase the square of many kinds of them , firstly like mulberry, unripe dates ,azarole, jujube , loquat, myrtle, wild pears,  khaki , and other types .